Memo to Brown floor leaders - Al Lowenstein:::::: (1976)
This memo to Brown floor leaders outlines plans to organize a strong show of support for Governor Jerry Brown on the convention floor on Wednesday, July 14. It instructs leaders to pick up prepared signs, banners, and flags from the Brown trailer before the session and explains that Brown will be the fourth candidate nominated, following Carter, McCormack, and Udall. Governor Brown is to be nominated by Cesar Chavez, with seconding speeches by Congresswoman Yvonne Braithwaite Burke and Governor Edwin Edwards. Delegates are directed to hold Brown signs until the end of Chavez's nominating speech, when they should wave signs, banners, flags, and state standards to create a coordinated demonstration of support.